Soret and Dufour effects on free convective heat and solute transfer in fluid saturated inclined porous cavity - Chandra Shekar Balla; Kishan Naikoti (Engineering Science and Technology, an International Journal, 2015)
The present problem addresses double diffusive free convection in an inclined square cavity filled with fluid saturated porous medium under the influence of Soret and Dufour effects. The inclined cavity makes an angle with the horizontal plane. At the two horizontal walls of the cavity the heat and solute transverse gradients are applied and lateral walls of the cavity are being regarded insulated and impermeable. Using the appropriate dimensionless quantities, the governing equations with boundary conditions are transformed to non-dimensional form. The governing partial differential equations are solved by Finite element method of Galerkin weighted residual scheme. Numerical results are obtained for different values of the Rayleigh number, Lewis number, buoyancy ratio, Soret Number and Dufour number. The overall investigation of variation of streamlines, isotherms, iso-concentration, Nusselt number and Sherwood numbers are presented graphically. To examine the accuracy, the present results are compared with the available results.